Edukasi Budidaya dan Pemanfaatan Azolla Melalui Komunitas Azo.co dengan Pendekatan Partisipatif - Salman Al Muhamadi; Mohammad Haekal Zen Arifin; William Andanu Purwanto; Shabrina Putri Fauziah; Akbar Dicky Muzadi; Etriya Etriya (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Azolla is beneficial for sustainable farming as a feed source, biofertilizer, and phytoremediator. This plant is potentially produced in Temuguruh Village, Banyuwangi Regency, East Java, which has a youth organization whose members have an average of 20 hours of free time per week. This community service program aims to educate the youths in Temuguruh Village regarding the utilization and cultivation of Azolla, which may help them to be more productive. This program applied the participatory approach and participatory communication, encouraging the youths (as the partners of this program) to be more proactive in participating in this program by using a community as a media outlet, namely Azo.co. This program develops the skills of the Azo.co members in the cultivation, utilization, and marketing of Azolla. Furthermore, the participatory approach and communication encourage Azo.co members to actively participate in learning within the community. Azo.co may follow up this program by partnering with other local communities, such as the fish farming community (Kelompok Pembudidaya Ikan).